Nexus between intellectual capital and profitability: evidence from listed SMEs in Malaysia / Hapsah S. Mohammad - Mohammad, Hapsah S. (Accounting Research Institute (ARI), 2022)
This paper examines the impact of intellectual capital and its components on profitability using the Modified Value Added Intellectual Coefficient (MVAIC) methodology. Data was collected from 26 listed SMEs in Malaysia from 2017-2019 providing 78 observations. This study employed the fixed-effect and random-effect models. The results showed that the MVAIC was significant and positively associated with profitability. Of the four components of the MVAIC, human capital efficiency and capital employed efficiency correlated positively and significantly with profitability. Structural capital efficiency was negatively associated with profitability. While, relational capital efficiency revealed an insignificant association with profitability. Overall, listed SMEs profitability was driven by both intellectual capital and physical capital, however the magnitude of contribution varied. The effect of capital employed efficiency presented a superior relative magnitude in comparison to human capital, structural capital and relational capital suggesting that physical capital was the main drive behind profitability. This study presented a robust theoretical foundation and employed a validated methodology. Therefore, it extends knowledge of intellectual capital among academicians and stakeholders as well as highlights its contribution to value creation.